Biblical Study On The Tolerance Of People Religion To Christians In Indonesia - Johanes Witoro (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study was motivated by various events that arose on the issue of Ethnicity, religion,race and inter-group relation in Indonesia, there had been issues of Ethnicity, religion,race and inter-group relation which led to attacks on each other, in online media or in person. This is the concern of the Indonesian government. This study uses a qualitative research method using Biblical studies as a basis and is supported by books related to this topic of discussion. Christ is a figure who is an example in the Christian faith, so from the example of Christ, love is the basis for a tolerant life. Christian exemplary life in community life guides in coexistence with others. Christians in Indonesia have understood and practiced the 1945 Constitution and Pancasila as the basis for democratic life and tolerance between religious communities. The teachings of Jesus Christ have been embedded as teachings that must be reflected in the life of the nation and state. Christians are people who are taught to obey the government in which they are located.